THE HIGHER EDUCATION INSTITUTION AND ITS RESOURCES - CICHON, Seweryn (Trends in education, 2013)
The higher education institution as an organization relies on a number of specific resources in the destination of the conduct of teaching and research. To the university's resources include: staff with the division in to scientists and the administrative staff, scientific- research equipment, library resources, archive sand buildings. For effective education institution must use all the resources at its disposal.
Keywords: resources; education; higher education institution